Identification and Examination of Scabies (Sarcoptes scabiei) in Cats at the Ganding Animal Clinic Sumenep Regency - Murtafiatun; Enni (Bioconsortium : Biological Research and Education, 2024)
Scabies in cats is an infectious skin disease caused by infestation with the mite Sarcoptes scabiei or Notoedres cati. Scabies is very contagious, both between cats and from cats to humans (zoonosis). This research aims is to find out what symptoms can cause scabies in cats and how the prevention stages and healing are for cats exposed to scabies at the Ganding Animal Clinic. This research uses quantitative descriptive methods. The results of observations at the Ganding Animal Clinic were that cats exposed to scabies would first be diagnosed through clinical examination and microscopic confirmation of skin scrapings. Then, treatment involves the use of antiparasitics such as ivermectin or selamatectin, accompanied by supporting treatments to reduce symptoms and prevent secondary infections. Prevention can be done by maintaining a clean environment, controlling the stray cat population, and regular inspections. Common symptoms experienced by cats exposed to scabies at the Ganding Animal Clinic are fever with body temperature increasing to 40°C and a rash on the ears and cats often scratching itchy parts of the body. With proper treatment, the prognosis for scabies in cats is generally good, but special attention is needed in severe cases or complications involving secondary infections.